Development of PEG-PCL-based polymersomes through design of experiments for co-encapsulation of vemurafenib and doxorubicin as chemotherapeutic drugs - D'Angelo, Natália A.; Câmara, Mayra C.C.; Noronha, Mariana A.; Grotto, Denise; Chorilli, Marlus [UNESP]; Lourenço, Felipe R.; Rangel-Yagui, Carlota de O.; Lopes, André M. (Elsevier, 2022)
Nanostructures for co-encapsulation of chemotherapeutic drugs have been widely studied for the last years due to its important advantages, e.g. improved bioavailability and cellular uptake, increased solubility of drugs, and lower chances of multidrug resistance (MDR). In this context, this work describes essential parameters of production and characterization of poly(ethylene glycol)-block-poly(ε-caprolactone) (PEG-PCL)-based polymersomes (Ps) for the co-encapsulation of two chemotherapeutic drugs, doxorubicin (DOX) and vemurafenib (VEM). Three PEG-PCL copolymers were studied, namely PEG45PCL44, PEG114PCL98, and PEG114PCL114. We evaluated the effect of conditions such as stirring speed, stirring time, hydration volume, and ultrasound time in particle size (DH) and polydispersity index (PDI) by two statistical designs (23) to achieve improved (smaller) DH and PDI of PEG-PCL-based Ps. According to our results, the best condition to generate PEG-PCL-based Ps was to employ 1050 rpm of stirring speed by 42 h, a hydration volume of 15 mL (0.05% m/v), and ultrasound by 35 min, resulting in a DH and PDI range of 210 to 245 nm and 0.117 to 0.148, respectively. Moreover, co-encapsulation of DOX and VEM resulted in drug loading ranges of 12 to 18% and 16 to 26% and encapsulation efficiency of 35 to 39% and 43 to 55%, for DOX and VEM, respectively, together with an increase in the DH (i.e., 254 to 282 nm). The Ps nanoformulations were stable at 4, 25, and 37 °C and the release of drugs was faster with the smaller PEG-PCL blocks (i.e., PEG45PCL44 > PEG114PCL98 > PEG114PCL114). The PEG-PCL-based Ps also demonstrated higher drugs release in an acidic environment (i.e., pH 5.0 at 37 °C, found in tumor cells) compared to physiological conditions (pH 7.4 at 37 °C). In conclusion, the DOX/VEM-PEG-PCL-based Ps may be a promising approach to cancer therapy with potential synergic effect, lower dosage, and lower risk of causing MDR.
Keywords: Design of experiments (DoE); Doxorubicin (DOX); Drug delivery systems (DDS); PEG-PCL copolymers; Polymersomes (Ps); Vemurafenib (VEM)